2019
DOI: 10.1002/jpln.201900043
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure of humus acids in soils

Abstract: The molecular structure of humus acids remains one of the most challenging issues in the soil science. The focus of the current research lies in defining the molecular and supramolecular structure of soil humus acids. This paper provides a brief review of the current understanding of the problem and shares findings of the elemental and X‐ray structural analysis of humic and fulvic acids extracted from Chernozems and Chestnut soils in the Rostov region. This region occupies a large area of the South‐European Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“… 35 , 54 HAs are organized in sopramolecular soft and permeable clusters, exposing hydrophilic groups, whereas hydrophobic species are shielded in the interior. 55 , 56 These chemical features make HAs highly reactive with proteins. 57 Accordingly, they can interact with gelatin through noncovalent interaction, such as hydrophobic and electrostatic interactions, as well as H-bonds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 35 , 54 HAs are organized in sopramolecular soft and permeable clusters, exposing hydrophilic groups, whereas hydrophobic species are shielded in the interior. 55 , 56 These chemical features make HAs highly reactive with proteins. 57 Accordingly, they can interact with gelatin through noncovalent interaction, such as hydrophobic and electrostatic interactions, as well as H-bonds.…”
Section: Resultsmentioning
confidence: 99%
“…HAs are mixtures of relatively low molecular weight compounds, characterized by a great variety of functional groups, including quinone, phenol, carboxyl, and hydroxyl moieties. , HAs are organized in sopramolecular soft and permeable clusters, exposing hydrophilic groups, whereas hydrophobic species are shielded in the interior. , These chemical features make HAs highly reactive with proteins . Accordingly, they can interact with gelatin through noncovalent interaction, such as hydrophobic and electrostatic interactions, as well as H-bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Essential components of this process are plant lignin, its transformation products, polysaccharides, melanin, cutin, proteins, lipids, nucleic acids and fine coal particles (Bezuglova, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, humus compounds are a humus matrix of complex multilevel organization (Fedotov and Dobrovolskiy, 2012). It was also found that the supramolecular organization of HAs in Chernozems and Kastanozems can be described as a spatial structure composed of 2-4 layers of condensed aromatic systems supplemented by a network of chain fragments with different degrees of regularity and lengths (Bezuglova, 2019). The purpose of this work is to study the identification features of humus in the process of long-term transformation through successive stages of the extraction of specific humic substances from a typical organogenic substrate (greenhouse soils) using alkaline and acid reagents.…”
Section: Introductionmentioning
confidence: 99%